APRAXIA AND ASSOCIATED FEATURES AT PRESENTATION IN DEMENTIA. Issue 10 (9th September 2014) - Ahmed, Samrah; Baker, Ian; Husain, Masud; Thompson, Sian; Butler, Chris
Abstract : Introduction: Limb apraxias, associated with disruption to the parietal lobe, have been commonly observed in various dementia syndromes. Parietal impairment also produces a range of other symptoms, including deficits in reading, writing and arithmetic. Aim: The aim of this study was to determine the profile of these features in Alzheimer's disease (AD) and Fronto-temporal dementia (FTD) spectrum disorders, at initial clinical presentation. Method: A total of 85 patients:10 posterior cortical atrophy (PCA), 8 logopenic aphasia (LPA), 17 AD, 13 behavioural variant FTD, 6 progressive non-fluent aphasia (PNFA), 6 semantic dementia (SD), and 25 patient with subjective memory impairment (SCI) were recruited from the Oxford Cognitive Disorders Clinic. Retrospective case note analysis of initial clinical interview and neurological examination was undertaken. Results: The prevalence of limb apraxia was highest in AD, LPA and PCA, and in PNFA. AOS was only observed in PNFA, present in all but one patient. The presence of other parietal features was highest in the AD spectrum disorders. Discussion: The results suggest that simple clinical examination for the presence of apraxia and associated left parietal features at initial presentation can assist in differential diagnosis of AD and FTD spectrum disorders that typically show overlapping features.